The Effect Of Government Services On Village Development In Sei Buluh Perbaungan District - Anjas Tammah; John F Marpaung (Institute of Computer Science (IOCS), 2021)
This study aims to determine: The effect of government services on village development in Sei Buluh, Perbaungan sub-district. Services area form of activity carried out by government agencies at the regional center, in the form of goods and services in the context of meeting community needs in accordance with the prevailing laws and regulations.This type of research is quantitative research. The sample used in this study were residents of the village of Sei Buluh, Perbaungan district. Number of Samples Using the Slovin formula quoted by Savilla in his book Sadarmayanti and Syarifudin Hidayat, the total sample size is 74 people from a population of 275 people. The technique used for data collection is using a questionnaire (questionnaire). The data analysis technique used is simple linear regression. The results of this study indicate that the independent variable of government services has a positive and significant effect. The contribution of the influence of government services on village development can be seen from the value of t count> t table with a count value of 2.083> 1.985 and significant 0.000 <0.05.